DIGITAL PLATFORMS AND ECOSYSTEMS: THE DRIVING FORCES OF THE GLOBAL ECONOMY - BRECHKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the essence and differences between digital platforms and ecosystems, their importance and role in the modern global economy and the impact on the development of innovations and the digital global space. The purpose of the article is to study the features of digital platforms and ecosystems, key aspects of their functioning, common and distinctive features between them and creating value for users, as well as identifying the driving forces of development and assessing their impact on innovation in the context of digitalization and globalization of the economy. To achieve the goal, the methods of scientific literature analysis, statistical data, as well as the analysis of well-known examples of successful digital platforms and ecosystems were used. An overview of modern trends in the development of digital technologies and their impact on the global economy was conducted. Based on the conducted research, the article presents the results of the analysis of the role of digital platforms and ecosystems in the global economy. The key success factors of such ecosystems are considered, the main development trends and their negative aspects are revealed. Multifunctional platforms are also considered and their advantages are determined, and the peculiarities of their formation in the digital space are shown on the example of cryptocurrency ecosystems. The main provisions of the article can be used by domestic business entities to determine the priority areas of digitization and build their own digital platforms and ecosystems based on them. Further research could be aimed at deepening the understanding of the impact of digital platforms and ecosystems on the global economy by analyzing their role in specific industries and sectors, such as finance, trade, healthcare, education. It is also possible to study their impact on the stability and growth of the economy, as well as their role in creating new jobs and changing the forms of interaction between labor market participants. It is also important to study the impact of digital platforms on the level of inequality in the economy and ways to reduce possible negative consequences arising from their activities.